2006
DOI: 10.2190/a465-356m-7652-783r
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Loneliness and Social Support with College Freshmen's Academic Performance and Persistence

Abstract: Based on Tinto's (1993) model of academic persistence, this study investigated the relationship of loneliness, social support, and living arrangements with academic persistence decisions of 401 college freshmen. Participants completed a series of standardized instruments during class time. Social support was negatively related to loneliness and positively related to academic persistence decisions. Less loneliness and more social support predicted more positive persistence decisions. Neither social support nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 18 publications
(40 reference statements)
9
123
0
1
Order By: Relevance
“…This is a 20-item, single factor scale with strong internal consistency (alphas ranging between 0.89 and 0.94), test-retest reliability (r a = 0.73), and convergent and construct validity (Russell 1996). While previous studies are not consistent in how loneliness directly affects GPA (Ginter and Dwinell 1994;Norman 2003), it can influence academic persistence (Nicpon et al 2006). Students who are not socially integrated into an institution are at higher risk for dropping out (Tinto 1993), and loneliness is an indicator of social integration.…”
Section: Covariate Measuresmentioning
confidence: 99%
“…This is a 20-item, single factor scale with strong internal consistency (alphas ranging between 0.89 and 0.94), test-retest reliability (r a = 0.73), and convergent and construct validity (Russell 1996). While previous studies are not consistent in how loneliness directly affects GPA (Ginter and Dwinell 1994;Norman 2003), it can influence academic persistence (Nicpon et al 2006). Students who are not socially integrated into an institution are at higher risk for dropping out (Tinto 1993), and loneliness is an indicator of social integration.…”
Section: Covariate Measuresmentioning
confidence: 99%
“…Furthermore, students often do not have regular contact with fellow students in a MOOC; work is in most cases done individually (Toven-Lindsey et al 2015). Without collaboration, there is also a lack of peer support, making it harder for students to stay motivated (Bank et al 1990;Nicpon et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…There are many studies related to different aspects of Internet addiction. Researchers have found that psychological traits such as low self-esteem, shyness (Davis, 2001;Kim, & Davis, 2009;Niemz, Griffiths, & Banyard, 2005), poorly adapted person: introvert (Cao & Su, 2006;Griffiths & Dancaster, 1995;Huang et al, 2010), sadness, anxiety (Huang et al, 2010;Kim et al, 2006;Young, 1998), neuroticism (Cao & Su, 2006;Kim, Namkoong, Ku, & Kim, 2008;Ehrenberg, Juckes, White, & Walsh, 2008), a high sense of loneliness and sadness (Kim & Davis, 2009;Nicpon et al, 2006;Pawlak, 2002), social retreat (Griffiths & Dancaster, 1995), having maladaptive self-regulatory strategy (Spada, Langston, Nikčević, & Moneta, 2008), predisposition to social disinhibition (Niemz, Griffiths, & Banyard, 2005) are all significantly correlated with problematic Internet use.…”
Section: Introductionmentioning
confidence: 99%